2018
DOI: 10.1097/pcc.0000000000001600
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations on the Indications for RBC Transfusion for the Critically Ill Child Receiving Support From Extracorporeal Membrane Oxygenation, Ventricular Assist, and Renal Replacement Therapy Devices From the Pediatric Critical Care Transfusion and Anemia Expertise Initiative

Abstract: Further research surrounding indications, risks, benefits, and alternatives to RBC transfusion in children on extracorporeal devices is clearly needed. Using a structured literature review and grading process, the Transfusion and Anemia Expertise Initiative panel concluded that there is currently insufficient evidence to recommend specific RBC transfusion variables in children requiring extracorporeal membrane oxygenation, ventricular assist device, or renal replacement therapy support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…In adults, evidence supports restrictive transfusion practices in critically ill patients and hemoglobin thresholds for RBC transfusion of 7 or 8 g/dL appear safe and may be associated with improved outcomes . Application to adults undergoing ECMO suggests that restrictive transfusion practices are safe, although substantial variability in practice exists . Similar results have been observed in critically ill pediatric patients, where restrictive transfusion strategies are now routinely employed .…”
Section: Discussionmentioning
confidence: 62%
“…In adults, evidence supports restrictive transfusion practices in critically ill patients and hemoglobin thresholds for RBC transfusion of 7 or 8 g/dL appear safe and may be associated with improved outcomes . Application to adults undergoing ECMO suggests that restrictive transfusion practices are safe, although substantial variability in practice exists . Similar results have been observed in critically ill pediatric patients, where restrictive transfusion strategies are now routinely employed .…”
Section: Discussionmentioning
confidence: 62%
“…Research questions 1.5 and 1.6: summary of findings . – We recommend further research aiming to identify the appropriate Hb concentration in combination with physiologic markers (first research question) that should guide administration of RBC transfusion in combination in subpopulations of hemodynamically stable not covered in current recommendations, in hemodynamically unstable critically ill children (77), in patients with neurological insult (traumatic brain injury, stroke, intracranial hemorrhage) (93), in sickle cell with stroke or undergoing minor surgical procedures (94), in non-hemorrhagic shock undergoing acute resuscitation (77), in patients on ECMO or ventricular-assist device (VAD) (95).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, if the Hb level is > 7 g/dL, a RBC transfusion is not indicated in most PICU patients who are hemodynamically stable (33). More data are needed before this threshold of 7 g/dL can be generalized to all PICU sub-populations (see other papers of this supplement), namely children with respiratory failure (109) acquired and congenital cardiac disease (79), shock (77), severe hemorrhage (110) neurological insult (93) congenital anemia (94), cancer (94) and children exposed to devices like ECMO, ventricular assist device (VAD) and renal replacement therapy (95). The approach to transfusion decision making is unclear not only for patients who belong to these subpopulations, such as patients with sickle cell disease, but also for PICU patients with Hb level between 5 and 7 g/dL and in hemodynamically unstable patients; as such, we need to undertake RCTs to address the question.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies in adults being supported with ECMO for ARDS have demonstrated hemoglobin concentration of 70 g/L can be used without a significant change in clinical outcomes for the patient while reducing transfusion volume 140,141 . An expert panel review in 2018 could find no evidence for any specific target hemoglobin concentration, and recommended that the decision to transfuse should be based on evidence of inadequate cardiorespiratory support, or decreased systemic or regional oxygen delivery, rather than a fixed hemoglobin or hematocrit 142 …”
Section: Transfusion Thresholdsmentioning
confidence: 99%